Surgical management of blunt pancreatic transection. Issue 5 (November 2020) - Matsumoto, Shokei; Shimizu, Masayuki; Maekawa, Natsuho; Yamazaki, Motoyasu; Kitano, Mitsuhide
Abstract : Supplemental digital content is available in the text.